3(2x+7)=3

Simple and best practice solution for 3(2x+7)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+7)=3 equation:


Simplifying
3(2x + 7) = 3

Reorder the terms:
3(7 + 2x) = 3
(7 * 3 + 2x * 3) = 3
(21 + 6x) = 3

Solving
21 + 6x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + 6x = 3 + -21

Combine like terms: 21 + -21 = 0
0 + 6x = 3 + -21
6x = 3 + -21

Combine like terms: 3 + -21 = -18
6x = -18

Divide each side by '6'.
x = -3

Simplifying
x = -3

See similar equations:

| 4y^2-12y=0 | | x-2/2=x/4 | | x=16t^2+64t+22 | | 8=-.40x+4 | | x=-16t^2+64+160 | | x^2=69 | | (14x+2)+(11x+3)= | | x=5x^2-30x+181 | | 79-3x=33x+23 | | 2x+5=23-5x | | 4w-19/(2)+w+1/(10)=-1 | | 4w-19/(2)+w+1/(2)=-1 | | 1/7(x+7)=5 | | 8x^2-24x-30=5x^2-25x | | 4w-19/2+w+1/10=-1 | | 8-N=2(N-14) | | N-7=8+2X | | 54w^2-150= | | 7(4-3z)+3=-6(x-4)-8 | | 8(x+3)=2(x+36) | | 3(x-6)=12-3x | | 8=-40x+4 | | 6x-3=67-8x | | 7x=5(x+2) | | 8x^2-20x-2= | | 3(g-2)+10=3G+4 | | x-2x+1=0 | | -2t+4x=5 | | x^3+9a=0 | | x^2-9a=0 | | 2x^2-10x-600=0 | | 5x-14=3x+14 |

Equations solver categories